2015
DOI: 10.5966/sctm.2014-0296
|View full text |Cite
|
Sign up to set email alerts
|

Placental Mesenchymal Stromal Cells Rescue Ambulation in Ovine Myelomeningocele

Abstract: Myelomeningocele (MMC)-commonly known as spina bifida-is a congenital birth defect that causes lifelong paralysis, incontinence, musculoskeletal deformities, and severe cognitive disabilities. The recent landmark Management of Myelomeningocele Study (MOMS) demonstrated for the first time in humans that in utero surgical repair of the MMC defect improves lower limb motor function, suggesting a capacity for improved neurologic outcomes in this disorder. However, functional recovery was incomplete, and 58% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 56 publications
5
113
0
1
Order By: Relevance
“…We have shown that a large number of PMSCs can be obtained from a single donor and that they secrete high amounts of neurotrophic factors such as BDNF, HGF, and VEGF (19). In utero transplantation of PMSCs in the ovine SB model has shown pronounced recovery of hind limb motor function, and this effect was confirmed by decreasing the number of apoptotic cells at the site of injury in the retinoic acid-induced rat SB model (23,24,27). To further elucidate the paracrine function of PMSCs, we developed an in vitro apoptotic model and studied their paracrine neuroprotective function.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that a large number of PMSCs can be obtained from a single donor and that they secrete high amounts of neurotrophic factors such as BDNF, HGF, and VEGF (19). In utero transplantation of PMSCs in the ovine SB model has shown pronounced recovery of hind limb motor function, and this effect was confirmed by decreasing the number of apoptotic cells at the site of injury in the retinoic acid-induced rat SB model (23,24,27). To further elucidate the paracrine function of PMSCs, we developed an in vitro apoptotic model and studied their paracrine neuroprotective function.…”
Section: Discussionmentioning
confidence: 95%
“…MSC-derived exosomes (MSC-exosomes) have been used as a treatment for diseases and disorders of many systems such as the cardiovascular, neurological, musculoskeletal and immune systems [5,6,8,31]. Rats with traumatic brain injury exhibited significant functional recovery, increased neurite remodelling, angiogenesis and neurogenesis after treatment with exosomes [32].…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…Watanabe et al had only 1 lamb in the positive control group . The study by Wang et al allegedly aimed to demonstrate superiority of a 3‐layer SB closure with or without mesenchymal stromal cells . For such comparison, the sample size should have been of at least 10 surviving lambs per group to detect an expected difference between 0% for independent ambulation in the group without cells and 67% in the group with cells.…”
Section: Resultsmentioning
confidence: 99%